PENGARUH PEMBERIAN TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP TINGKAT STRES DALAM MENYUSUN SKRIPSI MAHASISWA TINGKAT AKHIR - Apriyanti; Sringati Sringati; Wendi Muhammad Fadhli (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Final year students often have stress during preparing a thesis such as writing difficulties. Thesis in final year students can affect students' psychological condition. Progressive musclerelaxation techniques, which can relieve physical and emotional tension, are one of theeffective solutions to manage the stress in preparing a thesis. This study aims to analyze theimpact of progressive muscle relaxation techniques toward the stress levels during preparingtheses of final year students at Widya Nusantara University.This type of research is quantitativewith pre-experimental using one group pre-test post-test design. The total of population in thisstudy was 147 final year nursing students of Widya Nusantara University and a total sample ofwas 25 respondents that taken by using purposive sampling technique. Univariate analysisshowed that 11 respondents who were previously in the severe and moderate stresscategories decreased to moderate stress, and 5 respondents had moderate stress categorydecreased to mild stress. The t-test on bivariate analysis showed a significance value of 0.000(p<0.05) with a difference of 0.92 (IK 95% 0.52 to 1.31). There is an impact of giving progressivemuscle relaxation techniques toward the stress levels during preparing a thesis of final yearnursing students at Widya Nusantara University. It is expected that education institution canintegrate stress management programs, such as progressive muscle relaxation techniques, tohelp students manage stress during thesis preparation, as well as provide counseling servicesand stress skills training.